Nodular colloid degeneration of the skin: Report of three cases with review and update - Alireza Ghanadan; Kambiz Kamyab-Hesari; Maryam Daneshpajouh; Kamran Balighi; Pedram Normohammadpour (Wolters Kluwer Medknow Publications, 2014)
Nodular colloid degeneration (NCD) is a rare dermatological disorder and uncommon type of colloid milium. The degeneration may be related to sun exposure. In this report, three cases, all presenting as multiple plaques and nodules over the nose and the face are depicted. Histologically, these nodular masses were homogeneous, with eosinophilic-cleaved materials expanding the papillary dermis and extending into the deep dermis. Periodic acid Schiff (PAS), crystal violet, and methyl-violet stains highlight the colloid material. All the three cases were finally diagnosed as NCD. NCD could be considered in any case with facial nodules and a long history of sun exposure. We suggest the long-term sun exposure as an etiologic factor; thus sun protection would be the most preventive and available treatment.